UNRAVELLING IDIOMATIC EXPRESSIONS IN TAYLOR SWIFT'S ALBUM "MIDNIGHTS": A QUALITATIVE ANALYSIS (Lectio: Journal of Language and Language Teaching, 2025)
This research investigates the idiomatic expressions present in Taylor Swift's album "Midnights." Employing qualitative research and content analysis, the songs from the album serve as the primary data source. Using Palmer's theory, the researcher collected the song lyrics by browsing various platforms, particularly Spotify, transcribing, and listening to them. The data analysis involved reading, identifying, and classifying the types and meanings of idiomatic expressions within the lyrics, culminating in drawing conclusions. The findings revealed three types of idiomatic expressions in the lyrics: phrasal verb idiom (67% - 37 idioms), partial idiom (9% - 5 idioms), and prepositional idiom (24% - 13 idioms). The idiomatic expressions were associated with two distinct meanings: denotative meaning (91% - 50 idioms) and connotative meaning (9% - 5 idioms). This study sheds light on the prevalence and types of idiomatic expressions in Taylor Swift's album "Midnights," providing insights into the richness of language use and its impact on the overall themes and emotions conveyed in the songs.